Developmental Programming of Thermonastic Leaf Movement - Park, Young-Joon (Plant Physiol, 2019)
Plants exhibit diverse polar behaviors in response to directional and nondirectional environmental signals, termed tropic and nastic movements, respectively. The ways in which plants incorporate directional information into tropic behaviors is well understood, but it is less well understood how nondirectional stimuli, such as ambient temperatures, specify the polarity of nastic behaviors. Here, we demonstrate that a developmentally programmed polarity of auxin flow underlies thermo-induced leaf hyponasty in Arabidopsis (Arabidopsis thaliana). In warm environments, PHYTOCHROME-INTERACTING FACTOR4 (PIF4) stimulates auxin production in the leaf. This results in the accumulation of auxin in leaf petioles, where PIF4 directly activates a gene encoding the PINOID (PID) protein kinase. PID is involved in polarization of the auxin transporter PIN-FORMED3 to the outer membranes of petiole cells. Notably, the leaf polarity-determining ASYMMETRIC LEAVES1 (AS1) directs the induction of PID to occur predominantly in the abaxial petiole region. These observations indicate that the integration of PIF4-mediated auxin biosynthesis and polar transport, and the AS1-mediated developmental shaping of polar auxin flow, coordinate leaf thermonasty, which facilitates leaf cooling in warm environments. We believe that leaf thermonasty is a suitable model system for studying the developmental programming of environmental adaptation in plants.